An INRS cause tree method assessment for complex accidents analysis: Application to the Fukushima Nuclear Power Plants accident. (February 2021) - Amorim, Ana Paula Alves; Figueiroa Filho, Celso Luiz Santiago; Assis, Edilson Machado de
Highlights: Innovative proposal in the application of CTM for a complex process accident. Criteria selection by AHP for complex accident analysis methods comparison. The INRS method characterizes each event in the evolution of the accident. The INRS CTM results better than NUREG FTA for descriptive and consequential criteria. Abstract: This article proposes a new approach to the Cause Tree Method (CTM) or also known as the INRS method (Institut National de Recherche et de Sécurité), with the aim of verifying its applicability for accidents in more complex environments, than they are often used, like work accidents. For this, the Analytic Hierarchy Process (AHP) methodology was used as a way of supporting the comparison with other accident investigation methods, in which, selected the most impacting criteria for the analysis of complex accidents. From which it allowed the comparison of the results of the analyses performed of the Fukushima accident by the NUREG - 0492 method and the INRS method.In addition, this is an innovative approach in the study of the Fukushima accident, since it makes it possible to know the influences of the main components in the occurrence of the accident and the spread of damage. It was observed that the INRS method obtains an advantage over the NUREG - 0492 method in 2 criteria of the 3 criteria selected as relevant in the investigation of complex accidents. In addition, to the analysis made of the accident, it is understood that although the geographic location of the nuclear station anticipates the occurrence of earthquakes and subsequent tsunamis, safety plans were inefficient to contain the damage. Thus, it is verified, through the comparative analysis between methods and case study, that the INRS method is a robust and viable option to assess complex accidents.